Vulnerable to Precarity: COVID-19 and the Experience of Difference by Newcomers, Immigrants, and Migrant Workers in Canada - Karki, Karun Kishor; Moasun, Festus Y. (Molung Educational Frontier, 2023)
When COVID-19 struck Canada in 2020, immigrants, newcomers, and migrant (agricultural) workers were among those most vulnerable to the pandemic. Their experiences of the pandemic were accentuated by an exacerbation of pre-existing racial and other forms of discrimination. The article emerged from a systematic review and thematic synthesis of the broadly defined literature on immigrants, newcomers, and migrant workers’ experiences of multifaceted challenges amid the COVID-19 pandemic in Canada. We established inclusion criteria and systematically searched for articles in databases, including JSTOR Journals, Social Work Abstract (EBSCOhost), PsycINFO, and other grey literature published between March 2020 and January 2023. The findings suggest that immigrants, newcomers, and migrant workers in Canada experienced systemic inequalities, which worsened their socio-economic status, placing them at higher risks of poor health outcomes. The following themes that underscore the experiences of immigrants, newcomers, and migrant workers in Canada were identified: a) that immigrants, newcomers, and migrant workers in Canada experienced negative socio-economic impacts due to COVID-19, b) that immigrants, newcomers, and migrant workers in Canada experienced aggravated precarious and inequitable employment during COVID-19, c) that immigrants, newcomers, and migrant workers in Canada experienced COVID-19 related racial discrimination, and d) that COVID-19 negatively impacted immigrants, newcomers, and migrant workers’ mental health and well-being. Important directions for future research, including for studies that prioritize new  immigrants, are provided.